Retórica y filosofía: la sofística en pleno dominio de la "negatividad" (2021)
This article propose a reflexive approach to the sophist response to what has been called the deployment of “negativity”, as a tentative replica of the impossibility of becoming the sensitive world established by Parmenides of Elea theory of being. In this sense, the “relativism” of the measured man (homo-mensura) of Protagoras of Abdera and the critical “nihilism” of the non-being of Gorgias of Leontinos are postulated as seditious strategies to resist the ontological encirclement that is being established at the time. That is why we can speak of the “sophistic pharmacy” in the sense that they use the instrument of logos as that potent drug that is both poison and remedy, but that allows them to develop an agonal dialectic as an alternative to metaphysical imposition. Sophistic is presented as a philosophy in the form antiphilosophy of , that is, another way of doing philosophy.